Production of recombinant proteins using prokaryotic and eukaryotic expression systems - Stemmer, Vitus (Jihočeská univerzita, 2020)
A recombinant enzyme PNGase H+ was produced in E. coli, and several steps were tried to optimize the expression, extraction and purification. Furthermore, PCR primers were designed to detect genes of predicted sialyltransferases, fucosyltransferases and DNA methyltransferases in Ixodes ricinus genomic DNA and plasmids were designed for future production of DNA methyltransferases in an insect expression system.
Production of recombinant proteins using prokaryotic and eukaryotic expression systems